Praktykant, czyli przyszły bibliotekarz. Refleksje opiekuna praktyk - Marciniak, Aleksandra (Acta Universitatis Lodziensis. Folia Librorum, 2014)
The main of the article is to show the importance of carefully preparation of training for students in the library. The person who takes care of the apprentices’ work should know the study curriculum and confront the training with it. What is more, everybody must be aware of the needs of both sides – the librarians and the students. This issue was shown from the point of view of the librarians from The Pedagogical Academy in Łódź who used to train students of University of Łódź for a few years. A special form with the list of tasks was prepared to enable a proper realization of the whole process.